Corruption prevention based on e-government with Islamic religiosity as a moderating variable / Chrisna Suhendi, Abdul Rohman and Agus Purwanto - Suhendi, Chrisna; Rohman, Abdul; Purwanto, Agus (Accounting Research Institute (ARI), Universiti Teknologi MARA (UiTM), 2020)
The growing phenomenon of corruption in Indonesia was used as a basis of this research. This study aimed to examine the effect of e-government on corruption and the role of Islamic religiosity in moderating the relationship between e-government and corruption. The research data was obtained through a survey of 133 of 869 Budget Users (PA) at the Local Government Work Unit (Organisasi Perangkat Daerah, OPD) in Central Java Province. Data analysis in this research used the SPSS 16 software aid with the Moderated Regression Analysis (MRA) Test, ie pure moderated test. This research formulated 2 hypothesis. The test results showed that e-government has no direct negative effects in reducing corruption, but Islamic religiosity plays a role in moderating the relationship between e-government and corruption in order to reduce corruption.